Photochemistry at Scale: Wireless Light Emitters Drive Sustainability in Process Research & Development. Issue 5 (6th December 2021) - Burek, Bastien O.; Duong, Hong Thu; Hochradel, Klaus; Sutor, Alexander; Rupp, Matthias; Heilmann, Eike K.; Lovis, Kai; Bloh, Jonathan Z.
Abstract: Carbon−carbon bond formation by dual Iridium‐Nickel photoredox catalysis has gained a lot of attention for late‐stage cross‐couplings of alkyls with aryls. However, the scalability of such reactions is greatly impeded by the poor light penetration depth into the strongly absorbing reaction media. Wireless internal illumination is a novel technique which circumvents the light penetration issue efficiently and therefore allows to scale photon‐driven reactions by conventional methods. Here we demonstrate that industrially relevant photoredox C−C couplings can be scaled seamlessly to different volumes, achieving qualitatively and quantitatively the same results at all scales. The use of conventional reactor types allows stirred, bubble column or fixed‐bed operation mode and is fully compatible with heterogeneous reaction mixtures. By minimizing reflection losses, we could also show a significant advantage in the reaction rate over an externally illuminated setup at the same light intensity. Abstract : Our study demonstrates a seamless scale‐up of photochemical C−C‐cross‐couplings of aryls and alkyls via dual Ir/Ni photoredox catalysis. The herein described novel type of internal illumination using wirelessly powered LEDs inside the reaction media allows for efficient scaling and intensification of those reactions, maintaining virtually identical reaction profiles over all scales. The system is readily applicable to other light‐driven reactions as well.